Micro leakage, posterior resin restoration, Ariston PHc composite - Abdul Majeed, Kais Raad (2012)
Microleakage contributes to post- operative sensitivity, recurrent decay and failure of restoration. This study is to evaluate the ability of composite resin to reduce microleakage by release of ions like Ariston PHc and Tetric ceram composite. Method 72 Cl V cavity were prepared in 36 teeth (extracted upper first premolar), one buccally and one palatally in each tooth, the cavities were located on the middle third of the crown. The teeth were randomly divided into three groups (24 cavities for each group); Group A: filled with Helio- molar radiopaque composite. Group B: filled with Tetric ceram composite. Group C: filled with Ariston PHc composite. After the teeth were filled, they were restored in normal physiological saline in an incubator at 37 Co . one third of each group ( 8 cavities ) were thermocycled for one day ( 30 cycle ) , 2nd third thermocycled for 10 days ( 300 cycle ) , and the last third thermocycled for 100 days ( 3000 cycle) , each cycle mean immersion of teeth in cold water 5 Co for 30 second than immersed in hot water 55 Co for 30 second. The apices of the teeth were blocked with cold cute acrylic resin and the crowns were coated with two layers of nail varnish except 1 mm around restoration. The teeth were than immersed in the 0.5 % basic fuchsin dye for 24 hours in 37 Coin incubators, and they were longitudinally buccolingually and the extent of the dye penetration was recorded. Results The results revealed that Tetric-ceram composite reduce the leakage at tooth-resin interface, and dye penetration was reducing with time of aging. Micro leakage , posterior composite resin restoration, Ariston PHc composite.